Mrp.Payakumbuh's Proposed Marketing Strategy Using the Boston Consulting Group (BCG) and SWOT Methods - Fauzan, Rahmad; Umam, Muhammad Isnaini Hadiyul; Suherman, Suherman; Hamdy, Muhammad Ihsan; Nur, Muhammad (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Mrp.Payakumbuh is a small and medium enterprise that has grown quite rapidly in producing clothes in Payakumbuh City. This research was conducted to analyze the marketing strategy of Mrp.Payakumbuh  using the BCG Matrix method and SWOT Analysis. The results of this study using the BCG matrix by calculating the market growth rate that Mrp.Payakumbuh  are located in the position of The Dogs at 7.7% and in the calculation of the relative market share that the position of Mrp.Payakumbuh faces a low market share and low market growth rate conditions with a value of 0.83. The results of the SWOT analysis have several parts, namely Internal Factors, External Factors, IE Matrix, and effective marketing strategies in increasing sales of Mrp.Payakumbuh. Effective Company Strategy in Increasing Sales of Mrp.Payakumbuh is with the S-O Strategy (Strengths-Opportunitties utilizing promotional media for customers who repost purchases, making discounts, discounts at each specific event, and maintaining and improving the quality of products. The S-T (Strengths-Opportunitties) strategy sets prices according to changes in raw material prices, continues to pay attention to customer needs without harming the company, and adds several new types of products by paying attention to quality in order to compete with other companies. W-O Strategy (Weaknesses Opportunities) increase capital by collaborating with investors at the local level.